Meningkatkan Pendidikan Berbasis Kearifan Lokal untuk Anak Usia Dini di TK Bina Pelita Global - Dwiyani Angraeni; Azimatur Rahmi; Yossy Srianita; Helsy Julianty Edy (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Character education is a crucial aspect of early childhood education, as it shapes children's attitudes, behaviors, and understanding of moral values prevalent in society. This Community Service (PKM) initiative aims to enhance the competence of school principals and teachers in developing character education lessons grounded in Sundanese local wisdom, aligned with the Kurikulum Merdeka Independent Curriculum) for early childhood education. The activities were conducted at Bina Pelita Global Kindergarten in Tambun, Bekasi, employing a descriptive approach that included lectures, storytelling, discussions, and practical sessions on designing character education lesson plans. The program emphasized cultivating habits that reflect Sundanese cultural values, thereby fostering a love for local culture from an early age. The results indicate that teachers gained greater insight and improved skills in designing and implementing local wisdom-based character education programs in the classroom. Furthermore, students began to exhibit positive behavioral changes particularly in their appreciation and love for Sundanese culture rthough various habituation activities. The partner institution welcomed the program, recognizing its potential to support character development in students in a manner consistent with local cultural values and the needs of early childhood education.